Fate of nanostructured lipid carriers (NLCs) following the oral route: design, pharmacokinetics and biodistribution. (February 2014) - Beloqui, Ana; Solinís, María Ángeles; Delgado, Araceli; Évora, Carmen; Isla, Arantxazu; Rodríguez-Gascón, Alicia
Abstract The aim of this study was to develop a nanostructured lipid carriers (NLC) formulation containing spironolactone (SPN-NLCs), and to investigate its potential for the oral delivery of poorly water-soluble compounds. SPN-NLCs were orally administered to rabbits and the pharmacokinetics of spironolactone and its metabolites was evaluated. As reference formulation, we administered syrup. Spironolactone was only detected in a few plasma samples; hence, metabolite levels were employed for the pharmacokinetic analysis. The absolute bioavailability of 7α-TMS was significantly higher with the syrup than those obtained with the SPN-NLCs (0.7 versus 0.4, p < 0.05). However, no significant differences were observed in the bioavailability of canrenone, revealing a different canrenone/7α-TMS ratio depending on the administered formulation. Orally administered 99mTc-radiolabeled SPN-NLCs were mainly detected in the small intestine. These results suggest the retention of the nanocarriers in the underlying epithelium and further uptake by the epithelial cells.